A Review of the History of Sonography and its Effect on the Center for Medical Ultrasound at Wake Forest University. - Bullins, Adelia Thal (Journal of Diagnostic Medical Sonography, 2023)
A tremendous need for sonographers and vascular technologists exists, however it would be informative to look back at a time when a similar demand occurred. A review of the history of sonography is provided and how it impacted the Center for Medical Ultrasound at Wake Forest University. This historical review also marks the rise of early sonography education and how it evolved into a range of options such as a 4-year Bachelor of Science degree, a 2-year Associate Science degree, or a multiweek certificate program. No matter the length of the program, or the style in which it is delivered, the following basic key ingredients are considered requisite: • Access to newer model ultrasound equipment systems • Dynamic classroom lectures (online, live, or a combination of both) • Active clinical experiences under the guidance of an experienced and enthusiastic sonography expert, specific to a sonographic specialty (OB, cardiac, abdominal, etc.). Without all these key ingredients, the educational program will not be effective and sustainable. Sonography is a visual science and vital to display images, for the interpreting physician. The sonographer and physicians must work closely as a unified team. An effective working team (physician and sonographer) allows for trading ideas and suggesting possible answers to the diagnostically difficult patient cases.